1973
DOI: 10.2527/jas1973.372514x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amino Acids on Non-Protein Nitrogen Utilization by G-F Swine

Abstract: a Department of Animal Science. Acknowledgement is made to Fred Krieger in caring for the experimental animals and to John Welch for assistance in laboratory analyses and to Dawes Laboratories, Inc., Chicago, for providing the vitamin mixtures used in these studies. increased gain as compared to the gain of pigs fed the unsupplemented diets. This effect was not observed in pigs fed the 15% protein diets. Gain, feed consumption and backfat thickness of pigs were not significantly affected by the addition of ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…In the present study, supplementation of limiting amino acids improved F:G of G-F pigs (figure 3), but did not appear to make the NPN more useful to pigs or rats. Platter et al (1973) added amino acids to diets containing NPN and examined the effect on N retention in G-F pigs. A 10.9% protein opaque-2 cornsoybean meal diet supplemented with 3.1% protein equivalent from NPN (66% diammonium citrate, 6% monosodium glutamate and 28% glycine) was used as the control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, supplementation of limiting amino acids improved F:G of G-F pigs (figure 3), but did not appear to make the NPN more useful to pigs or rats. Platter et al (1973) added amino acids to diets containing NPN and examined the effect on N retention in G-F pigs. A 10.9% protein opaque-2 cornsoybean meal diet supplemented with 3.1% protein equivalent from NPN (66% diammonium citrate, 6% monosodium glutamate and 28% glycine) was used as the control.…”
Section: Resultsmentioning
confidence: 99%
“…Feed intake, daily gain and N retention (as a percentage of intake) were all reduced by the additions of NPN. Platter et al (1973) also reported that the substitution of NPN (1.5% protein equivalent supplied by monoammonium phosphate) for soybean meal protein produced .no effect on body weight gains or feed consumption by pigs given either 12 or 15% protein diets. In a more definitive experiment, Platter et al (1973) added 3.1% protein equivalent from NPN to a 10.9% crude protein opaque-2 corn-soybean meal diet.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Replacing crude protein in the diet with an equimolor mixture of diammoniura citrate and diammonium phosphate did not significantly depress performance of growing pigs until 20% or more of the crude protein equivalent was replaced(Wehrbein et al, 1970). However, in most cases, additions of nonprotein N did not affect growth(Platter et al, 1973; Zimmerman, 1975;Taylor et al,, 1981). Allen and Baker (1974) suggested that glycine, when supplemental levels are greater than 2% in chick diets, acts as an anorectic agent.…”
mentioning
confidence: 99%